2017
DOI: 10.1002/cbm.2043
|View full text |Cite
|
Sign up to set email alerts
|

Multiple traumatic experiences, post‐traumatic stress disorder and offending behaviour in female prisoners

Abstract: Women who have experienced multiple traumatic events may be more likely to commit serious offences, so it is very important to assess and meet their trauma-related needs. While prisons should never be used as substitutes for healthcare facilities, when women or girls are sent to prison, the opportunity for constructive interventions must be seized. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 27 publications
4
26
0
4
Order By: Relevance
“…We found that 59.4% screened positive for DSM-5 PTSD as measured by PCL-5 with a high prevalence of at least one type of reported prior trauma exposure (92.0%), 36.8% had pathological levels of dissociation, 70.4% had poor sleep quality, and 37.8% had clinical level of insomnia. The high rates of probable DSM-5 PTSD caseness and multiple trauma exposure, as well as significant relations with dissociative symptomatology were comparable with the previous studies (Akyuz et al, 2007;Briere et al, 2016;Cusack et al, 2013;DeCou et al, 2016;Henrichs & Bogaerts, 2012;Karatzias et al, 2017;Sindicich et al, 2014;Steiner et al, 1997).…”
Section: Discussionsupporting
confidence: 88%
“…We found that 59.4% screened positive for DSM-5 PTSD as measured by PCL-5 with a high prevalence of at least one type of reported prior trauma exposure (92.0%), 36.8% had pathological levels of dissociation, 70.4% had poor sleep quality, and 37.8% had clinical level of insomnia. The high rates of probable DSM-5 PTSD caseness and multiple trauma exposure, as well as significant relations with dissociative symptomatology were comparable with the previous studies (Akyuz et al, 2007;Briere et al, 2016;Cusack et al, 2013;DeCou et al, 2016;Henrichs & Bogaerts, 2012;Karatzias et al, 2017;Sindicich et al, 2014;Steiner et al, 1997).…”
Section: Discussionsupporting
confidence: 88%
“…Most studies were conducted in high income countries, with the majority (n = 21) conducted in the USA, four studies conducted in Europe [31, 35, 39, 55], and five studies (three reporting on the same sample) from the UK [47, 48, 50, 56, 58]. 22 studies reported on adult prisoners [3960], while 14 reported on incarcerated youth [26–38, 61].…”
Section: Resultsmentioning
confidence: 99%
“…The additional trauma endured by a mother when she is deemed a threat so severe that policy mandates that her child be taken away immediately after birth exacerbates the stigma and trauma that incarcerated women have already experienced. In a study by Karatzias et al, nine in 10 incarcerated females reported having experienced childhood and adult trauma, and more than half met the criteria for having posttraumatic stress disorder (PTSD) 41 . The majority of individuals reported multiple traumas, including childhood neglect and emotional, sexual or physical abuse, among others 41 .…”
Section: Benefits and Risks To The Mothermentioning
confidence: 99%
“…In a study by Karatzias et al, nine in 10 incarcerated females reported having experienced childhood and adult trauma, and more than half met the criteria for having posttraumatic stress disorder (PTSD) 41 . The majority of individuals reported multiple traumas, including childhood neglect and emotional, sexual or physical abuse, among others 41 . It has also been shown that incarcerated women have an increased lifetime prevalence of PTSD, around 40%, compared with 6–9% in the general population 42,43 .…”
Section: Benefits and Risks To The Mothermentioning
confidence: 99%
See 1 more Smart Citation